Sovyet arşiv belgeleri ışığında, Sovyetler Birliği’nın Türkiye algısındaki değişim ve dış politikaya yansımaları (1939-1953) - Haciyev, Agil (My University, 2014)
İkinci Dünya Savaşına katılmayarak savaş dışı kalmayı başarmış olan Türkiye savaşın hemen ardından dönemin büyüyen gücü Sovyetler Birliğinin malum talepleriyle karşı karşıya kalmıştır. Egemenlik haklarıyla bağdaşmayan bu talepler karşısında Türkiye’nin atacağı adımlar devlet olarak kaderini belirleyecek ve Orta Doğu’daki dengeleri değiştirecekti. Tezde somut bir tehdit karşısında kalan Türkiye’nin uyguladığı dış siyaset ve bu siyaset sonucunda Sovyetlerin Türkiye algısındaki değişim irdelenmiştir. Türkiye’nin Batıya entegrasyonu yönünde attığı adımlar ve özellikle NATO üyeliği ile safını belli ettiği bu süreç, Sovyet arşivinden derlenen belgelerle ele alınmış, bu dönemde iki devlet arasındaki gerginliğin her iki devletin dış politikasına yansımaları araştırılmıştır.

Turkey, which was able to stay out of the war due to its implementation of the policy of “neutrality” during the Second World War, faced with known demands of Soviet Union, rising power of the period. The steps taken by Turkey in responce to these demands which were incompatible with its sovereign rights will be determining its destiny as a state and modify the balance in the Middle East. The foreing policy of Turkey with regard to the concrete threat and the changes in the Soviets’ perception of Turkey as a result of that policy are analysed in this thesis. The process where Turkey determined its course with its steps in the direction of the integration with West and especially with joining NATO, were studied using the original documents compiled at Soviet archives and also the reflections of the tension between Turkey and Soviet Union on the foreing policy of both countries were investigated.
Keywords: Dünya Savaşı, II; Sovyetler Birliği; Türkiye